(untitled) - Reid, Anthony (New Haven, 1988)
Reid gives numerous contemporary foreign accounts of life in Southeast Asia on the eve of western imperialism and colonialism in a skillful, analytical, and critical way. The bibliography is excellent, and many of the drawings are from contemporary sources. Highly recommended for academic/research collections.
Keywords: Southeast Asia,Đông Nam Á; History,Lịch sử